Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12885-021-09057-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of cystine and theanine attenuates 5-fluorouracil-induced intestinal mucositis and diarrhea by suppressing both glutathione level decrease and ROS production in the small intestine of mucositis mouse model

Abstract: Background Chemotherapy is frequently used in cancer treatment; however, it may cause adverse events, which must be managed. Reactive oxygen species (ROS) have been reported to be involved in the induction of intestinal mucositis and diarrhea, which are common side effects of treatment with fluoropyrimidine 5-fluorouracil (5-FU). Our previous studies have shown that oral administration of cystine and theanine (CT) increases glutathione (GSH) production in vivo. In the present study, we hypothes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…These pathways have been proved to be closely related to the occurrence and development of intestinal injury caused by chemotherapy. Chemotherapy agents such as 5-FU may damage intestinal mucosa by increasing intestinal permeability, promoting the release of inflammatory cytokines, strengthening the oxidative stress response, and accelerating the intestinal epithelial cell apoptosis, thus causing GR ( de Barros et al, 2018 ; Zhang et al, 2018 ; Yoneda et al, 2021 ). Li et al ( Zeng et al, 2020 ) reported that 5-FU might significantly increase the expression levels of apoptosis-related genes such as PUMA and Bax.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways have been proved to be closely related to the occurrence and development of intestinal injury caused by chemotherapy. Chemotherapy agents such as 5-FU may damage intestinal mucosa by increasing intestinal permeability, promoting the release of inflammatory cytokines, strengthening the oxidative stress response, and accelerating the intestinal epithelial cell apoptosis, thus causing GR ( de Barros et al, 2018 ; Zhang et al, 2018 ; Yoneda et al, 2021 ). Li et al ( Zeng et al, 2020 ) reported that 5-FU might significantly increase the expression levels of apoptosis-related genes such as PUMA and Bax.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org (Boeing et al, 2020). The content of antioxidases decreases or cannot remove superfluous ROS, resulting in elevated oxidative stress and cell injury (Yoneda et al, 2021). Moreover, convincing evidence have demonstrated that elevated expressions of inflammatory factors were strongly related to the destruction of enteric mucosa barrier (Tappenden, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive production of ROS and uncontrolled inflammatory symptoms could disturb enteric homeostasis, change the normal microflora and stimulate a sequence of acute reactions to injure cells and tissues, resulting in mucosa damage and mucositis ( Boeing et al, 2020 ). The content of antioxidases decreases or cannot remove superfluous ROS, resulting in elevated oxidative stress and cell injury ( Yoneda et al, 2021 ). Moreover, convincing evidence have demonstrated that elevated expressions of inflammatory factors were strongly related to the destruction of enteric mucosa barrier ( Tappenden, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mucositis is initiated by 5-FU by decreasing antioxidant glutathione (GSH) and increasing extracellular release of MPO which produces reactive oxygen species (ROS) that cause intestinal oxidative damage [31] . Another study on the effect of 5-FU on jejunum of rats concluded that it increased level of malondialdehyde (MDA) and up regulated of NF-κB signaling pathway within the jejunum, this caused disturbance of gut epithelial barrier [1,32,33] .…”
Section: Discussionmentioning
confidence: 99%